2004
DOI: 10.1265/ehpm.9.130
|View full text |Cite
|
Sign up to set email alerts
|

Evidence in Favour of Lifestyle Intervention for Cancer Prevention with Special Reference to Colorectal Cancer

Abstract: Randomized controlled trials are recognized as having the strongest type of study design for generating evidence on prevention of disease. They are, however, the most labor-and time-intensive and costly to conduct. Intervention studies on the recurrence of colorectal adenomas might serve as a model with relevance to the etiology of not only large bowel cancer but also other sites of neoplastic development. The results of intervention studies assessing the effect of calcium, antioxidants and fiber on the recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The analysis by Kindt et al also revealed that dopamine Gq signaling only affected habituation when animals were trained with a shorter 10 s ISI, but not a longer 60 s ISI . Interestingly, C. elegans only display long‐term memory for habituation following training with longer 60 s ISIs, and there is no evidence to date for a role of dopamine Gq signaling in long‐term habituation . Recently, we reported additional molecules that exert different effects on habituation at different ISIs .…”
Section: Molecular Evidence That Habituation At Different Isis Is Medmentioning
confidence: 82%
“…The analysis by Kindt et al also revealed that dopamine Gq signaling only affected habituation when animals were trained with a shorter 10 s ISI, but not a longer 60 s ISI . Interestingly, C. elegans only display long‐term memory for habituation following training with longer 60 s ISIs, and there is no evidence to date for a role of dopamine Gq signaling in long‐term habituation . Recently, we reported additional molecules that exert different effects on habituation at different ISIs .…”
Section: Molecular Evidence That Habituation At Different Isis Is Medmentioning
confidence: 82%